Periodontal ligament cells derived small extracellular vesicles are involved in orthodontic tooth movement. (18th August 2022) - Zhang, Yimei; Zhang, Ting; Zhang, Ziqian; Su, Junxiang; Wu, Xiaowen; Chen, Liyuan; Ge, Xuejun; Wang, Xiujing; Jiang, Nan
Summary: Objectives: Small extracellular vesicles (EVs) from human periodontal ligament cells (hPDLCs) are closely associated with periodontal homeostasis. Far less is known about EVs association with orthodontic tooth movement (OTM). This study aimed to explore the role of small EVs originated from hPDLCs during OTM. Materials and methods: Adult C57BL/6 mice were used. Springs were bonded to the upper first molars of mice for 7 days to induce OTM in vivo . To block small EVs release, GW4869 was intraperitoneally injected and the efficacy of small EVs inhibition in periodontal ligament was verified by transmission electron microscope (TEM). Tooth movement distance and osteoclastic activity were studied. In vitro, hPDLCs were isolated and administered compressive force in the EV-free culture media. The cell morphologies and CD63 expression of hPDLCs were studied. Small EVs were purified and characterized using a scanning electron microscope, TEM, western blot, and nanoparticle tracking analysis. The expression of proteins in the small EVs was further processed and validated using a human immuno-regulated cytokines array and an enzyme-linked immunosorbent assay (ELISA). Results: The small EV depletion significantly decreased the distance and osteoclastic activity of OTM in the mice. The hPDLCs displayed different morphologies under force compression and CD63 expression level decreased verified by western blot and immunofluorescence staining. Small EVs purified from supernatants of the hPDLCs showed features with <200 nm diameter, the positive EVs marker CD63, and the negative Golgi body marker GM130. The number of small EVs particles increased in hPDLCs suffering force stimuli. According to the proteome array, the level of soluble intercellular adhesion molecule-1 (sICAM-1) displayed the most significant fold change in small EVs under compressive force and this was further confirmed using an ELISA. Limitations: Further mechanism studies are warranted to validate the hPDLC-originated small EVs function in OTM through proteins delivery. Conclusions: The notable decrease in the OTM distance after small EV blocking and the significant alteration of the sICAM-1 level in the hPDLC-originated small EVs under compression provide a new vista into small EV-related OTM biology.